Theoretical basis and search for new methods of cardiac arrhythmias' pathogenetic therapy - V. M. Moroz; T. N. Lipnitsky (Российский кардиологический журнал)
Efficacy of cardiac arrhythmias (CA) pharmacotherapy does not exceed 70%; incidence of adverse effects, causing treatment discontinuation, is as high as 10-30%. The need for CA pharmacotherapy improvement is obvious. The authors propose new methods for CA pathogenetic treatment, based on normalization of barrier and distributional sarcolemma functions, and intracellular ion dysbalance correction. Antiarrhythmics normalizing ion channel function should be combined with membrano-protective agents (rhythmocor, salmagin, etc.).